Pengembangan Usaha Mikro, Kecil, Dan Menengah (Umkm) Melalui Dukungan Perbankan Islam: Tinjauan Empiris Di Indonesia - Aniq Akhmad Ali Bawafie; Sahria; Saiful Muchlis (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, contributing significantly to GDP, employment and job creation. However, the sustainability and development of MSMEs still face challenges, including limited access to financing, particularly from Islamic banks. This study aims to explore the role of Islamic banks in supporting the development of MSMEs in Indonesia through a documentation analysis approach. Results show that sharia-based financing, such as Mudharabah and Musyarakah, has great potential in improving financial inclusiveness, economic justice, and sustainability of MSMEs. However, the portion of Islamic bank financing for MSMEs is still low, with suboptimal financing quality. Collaborative strategies between Islamic banks, government, and technological innovation are needed to overcome financing access constraints and strengthen the role of MSMEs in achieving sustainable development goals. This study provides an important perspective on strengthening synergies between the Islamic banking sector and MSMEs as a key driver of inclusive economic growth